Kepemimpinan Publik di Tengah Krisis Kepercayaan Politik di Indonesia Menurut Filsafat Politik Niccolo Machiavelli - Paulus Febri Rabuni; FX. Eko Armada Riyanto (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
This article aims to critically examine the concept of public leadership through the philosophical perspective of Niccolo Machiavelli. The crisis of political trust is one of the main challenges in democratic life in Indonesia. This phenomenon is evident in the declining level of public trust in political institutions, public officials, and policy-making processes that are considered not fully in favor of the people's interests. This article explores Machiavelli's system of ideas about virtù and fortuna and analyzes the role of public leadership amidst the crisis of political trust in Indonesia using a political philosophy approach, specifically the dimensions of leadership ethics, public responsibility, and trust in power. The method used is a library study by examining political philosophy literature, specifically the book Dekolonisasi, as well as articles on leadership, ethics, and public trust. The results of the analysis show that the crisis of political trust is not only caused by institutional factors, but also by weak integrity, transparency, and accountability in leadership practices. Therefore, public leadership based on ethics, moral exemplars, and commitment to the public interest are essential requirements for restoring public trust. Thus, strengthening the ethical dimension in public leadership is a strategic step in strengthening the quality of democracy in Indonesia. The focus of this article is to demonstrate a Machiavellian framework for examining tolerance in the murky world of politics.